Integrated ABC–AHP–TOPSIS Model for Used Distribution Material Management at PLN UP3 Mamuju - Thomi; Niniet Indah Arvitrida (ENERGY: JURNAL ILMIAH ILMU-ILMU TEKNIK, 2026)
The management of used distribution materials at PT PLN UP3 Mamuju faces challenges related to idle inventory, dead stock, subjective decision-making, and the absence of a systematic prioritization framework. These issues reduce material utilization and limit the recovery of asset value. This study develops an integrated multi-criteria decision-making model by combining ABC Classification, the Analytical Hierarchy Process (AHP), and the Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) to support objective and structured management of used distribution materials. The novelty of this study lies in the integration of inventory classification, multi-criteria weighting, and alternative ranking within a single decision-support framework for distribution material management, complemented by an economic feasibility evaluation. ABC Classification was used to identify economically significant materials, AHP to determine the relative importance of decision criteria, and TOPSIS to prioritize management alternatives, including reuse, redistribution, scrap, and disposal. The results indicate that safety is the most influential decision criterion, while conductors and distribution cables represent the highest-priority materials for reuse. The proposed model improves decision consistency, increases material utilization, reduces inventory losses, and generates significant economic benefits with a highly feasible investment. Overall, the integrated ABC–AHP–TOPSIS framework provides a practical decision-support tool for improving operational efficiency, optimizing asset value recovery, and supporting sustainable distribution material management in electric utility companies.